Dissolution Kinetics of Calcined Ulexite in Ammonium Chloride Solutions. - GUR, A.; YILDIZ, A.; CEYLAN., H. (Asian Journal of Chemistry, 2010)
In this study, the leaching kinetics of calcined ulexite in ammonium chloride solutions were investigated. The effect of calcination temperature, solution concentration, reaction temperature and prehydration were chosen as parameters. It was observed that the rate of dissolution increased with increasing calcination temperature, solution concentration and reaction temperature, while it was not affected by prehydration. Employing graphical and statistical methods, the dissolution rate, based on homogeneous reaction model, can be shown as: (1 - X)-1 - 1 = k(NH4Cl)4/5. The activation energy for the dissolution of the ulexite sample calcined at 160°C was found to be 62.65 kJ mol-1.